2021
DOI: 10.1177/10406387211021411
|View full text |Cite
|
Sign up to set email alerts
|

Detection by real-time quaking-induced conversion (RT-QuIC), ELISA, and IHC of chronic wasting disease prion in lymph nodes from Pennsylvania white-tailed deer with specific PRNP genotypes

Abstract: Chronic wasting disease (CWD) is a prion-mediated, transmissible disease of cervids, including deer ( Odocoileus spp.), which is characterized by spongiform encephalopathy and death of the prion-infected animals. Official surveillance in the United States using immunohistochemistry (IHC) and ELISA entails the laborious collection of lymphoid and/or brainstem tissue after death. New, highly sensitive prion detection methods, such as real-time quaking-induced conversion (RT-QuIC), have shown promise in detecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…We found that our RT-QuIC results were comparable to those of the IHC and ELISA, with only 0.5% (7 samples out of 1,300) of discordant results between the three techniques when testing WTD RLNs ( Table 2 ). In previous studies that compared the three assays, 100% of matching results were observed ( 23 , 30 ). One possible explanation for the observed difference is the fact that the previous studies did not include as many positive WTD RLNs.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…We found that our RT-QuIC results were comparable to those of the IHC and ELISA, with only 0.5% (7 samples out of 1,300) of discordant results between the three techniques when testing WTD RLNs ( Table 2 ). In previous studies that compared the three assays, 100% of matching results were observed ( 23 , 30 ). One possible explanation for the observed difference is the fact that the previous studies did not include as many positive WTD RLNs.…”
Section: Discussionmentioning
confidence: 81%
“…The development of in vitro amplification assays, as protein misfolding cyclic amplification and RT-QuIC have helped to enhance the sensitivity of CWD prion detection in the last few years. The RT-QuIC assay has been reported to amplify PrP CWD seeds present in brain dilutions in the femtogram range ( 44 , 45 ) and has been used to detect PrP CWD in a variety of anatomic sites, body fluids, and excreta ( 13 , 22 30 ), but the technique has yet to be approved for official CWD surveillance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We employed weakly informative priors (i.e., distributions with higher uncertainty) for the Se and Sp estimates for ELISA/IHC because of the limited studies of performance available, of which the majority were applied under laboratory conditions or with limited sample size [ 29 , 31 , 32 , 64 ]. We assumed that ELISA and IHC accuracy was similar given the previous review available, indicating that both diagnostic assays performed similarly [ 45 ].…”
Section: Discussionmentioning
confidence: 99%